Physicochemical Parameters, Mineral Composition, and Nutraceutical Properties of Ready-to-Drink Flavored-Colored Commercial Teas - Flores Martínez, Daniel; Urías Orona, Vania; Hernández García, Luis; Rubio Carrasco, Werner; Silva Gutiérrez, Korev; Guevara Zambrano, Michelle; Prieto Cadena, Julio; Serna Méndez, Teresa Cecilia; Muy Rangel, Dolores; Niño Medina, Guillermo (2018)
The physicochemical parameters, mineral composition, and nutraceutical properties of ready-to-drink ﬂavored-colored commercial teas were analyzed in the present study. The pH of samples was slightly acidic (3.72 to 4.11), titratable acidity was low (0.092 to 0.174%), and color parameters were wide variable (pink, yellow, brown, and red). Citrus-ﬂavored tea obtained the highest content of manganese (0.281mg·L−1), zinc (0.069mg·L−1), magnesium (2.92mg·L−1), potassium (62.65mg·L−1), and sodium (271.74mg·L−1), while lemon-, peach-, and blueberry-ﬂavored teas obtained the highest levels of copper (0.035mg·L−1), iron (0.246mg·L−1), and calcium (18.21mg·L−1), respectively. Citrus, lemon-, sangria-, and rose petal-ﬂavored teas obtained the highest content in total phenols (211.56mg·L−1), total ﬂavonoids (65.46mg·L−1), total catechins (640.79mg·L−1), and total anthocyanins (640.79mg·L−1), respectively. Lemon- and rose petal-ﬂavored teas showed the highest and lowest antioxidant capacity levels in DPPH (1096.00 to 118.77μmolTE·L−1), ABTS (1048.84 to 232.00μmolTE·L−1), and FRAP (1269.20 to 147.70μmolTE·L−1) assays. The levels of sodium reported in labels of all samples were lower than data obtained in our analysis. Alsothelevelsobservedfortotalphenolsinblueberry-,citrus-,androsepetal-ﬂavoredteaswerelowerthanouranalysis,buttotal phenolsoflemon-,peach-,andsangria-ﬂavoredteaswerehigherthanthecontentreportedintheirlabels.Theresultsobtainedin thepresentworkgiveinformationtoconsumersforchoosingﬂavored-coloredready-to-drinkteabasedonthephysicochemical, nutritional, and nutraceutical properties.